Transportation resilience and food security: developing a conceptual framework through literature review - Hossain, Shahadat; Kashem, Shakil Bin (Frontiers in Sustainable Food Systems, 2025)
Ensuring food security depends heavily on the resilience of transportation networks, which are vital for the consistent distribution and accessibility of food. Disruptions to these networks, whether caused by natural disasters, structural failure, or other crises, can significantly impair food availability, accessibility, and affordability, exacerbating food insecurity. Despite the critical role of transportation systems, existing research often overlooks the nuanced relationship between transportation resilience and food security. This review paper addresses this gap by thoroughly examining the structural and functional components of resilient transportation systems and their direct influence on food security. Findings from the literature highlight the critical role of robust infrastructure, social equity and governance, redundancy and adaptive capacity for maintaining stable food supply for all communities during disruptions. Through a systematic literature review, we propose a conceptual framework that integrates transportation system components, resilience indicators, and food security outcomes, demonstrating how collectively considering these key elements within specific local and regional context can enhance food security and reduce vulnerability to crises. The framework offers valuable insights for planners and policymakers, suggesting targeted strategies to improve transportation resilience and, by extension, food security. By adopting this integrated approach, cities can better prepare for and recover from disruptions, ensuring sustainable development and resilience in the face of growing global challenges.